DISCURSOS MEDICALIZANTES NA EDUCAÇÃO INFANTIL: PROBLEMATIZAÇÕES EM TORNO DA EDUCAÇÃO ESPECIAL - Oliveira, Debora Nascimento de (2019)
This paper presents as a central question how the discourses include medicalization in the daily life of pre-primary education and how special education is brokered by such medicalizing discourses. By medicalization we mean the process of transforming soc